Utilization of Green Mussel (Perna viridis) as A Lead Metal Pollutant Adorbent in Batik Dye Waste - Pradipta, Savalda Rosca; Triastuti, Juni; Dewi, Nina Nurmalia (Universitas Airlangga, 2024)
Lead (Pb) from batik dyeing waste that is thrown into the environment can pollute the environment so it needs processing before being thrown into the environment. The aim of this research is to determine the effect of green mussel shells as an adsorbent with different concentrations on reducing Pb heavy metal contamination in batik dyeing waste and to determine the optimal concentration of green mussel shells to reduce Pb heavy metal contamination in batik dyeing waste. The research method used was experimental with 4 treatments with different concentrations of green mussel shell ash as an adsorbent (0, 10, 20, and 30%). The results of the research showed that a green mussel shell ash concentration of 30% was the best concentration because it was able to reduce Pb levels in batik dyeing waste by 68.52%. Characterization of green mussel shell ash includes average pore radius (10.674 nm), total pore volume (0.005 cc/g), and surface area (0.969 m2/g).